Determining feed budgets for farm-specific nutritional programs - Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1998)
Use of feed budgets simplifies feed delivery and improves the accuracy of delivering diets to the correct pig weight ranges during the nursery and finishing periods. Little information has been available for determining farm-specific feed budgets in the past. In this paper, we will outline simple methods to customize a feed budget for individual farms using feed efficiency from past closeout records.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Feed budgets; Farm-specific nutritional programs